Note: This article has been RETRACTED – Analysis of the Causes of Most Chinese Private Entrepreneurs’ Nonparticipation in Charity - Zhang, Leilei (Journal of Urban Culture Research, 2020)
Note: This article has been RETRACTED – Enterprise charity is not only an important way for enterprises to fulfill their social responsibility, but also related to their strategic development. However, most private entrepreneurs in China are not interested in doing charity. The purpose of this study is to explore the reasons why they do not participate in philanthropy. In-depth interviews were conducted with 14 charitable and 10 non-charitable entrepreneurs in 24 cities of 12 provinces in China. By applying continuous analytic induction, three-level coding with NVIVO software and comparative analysis, The results show that this is not due to the lack of economic strength of the enterprises, or the influence of China’s special national conditions, but because the entrepreneurs do not possess their own charity faith. It also provides a certain theoretical reference for entrepreneurs in other countries to fulfill their social responsibilities, In other words, to cultivate entrepreneurs’ sense of social responsibility, it is important to help them establish their charitable beliefs.